(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Thoracic epidural analgesia (TEA) is the reference standard for pain control after major abdominal surgery but is limited by sympathetic blockade, hypotension and a defined complication profile. The ultrasound-guided erector spinae plane block (ESPB) is a less invasive interfascial plane alternative. We compared the two techniques for intraoperative haemodynamic stability and postoperative analgesia. Methods: Seventy adults undergoing elective major open abdominal surgery were randomized to bilateral continuous ESPB (Group E, n = 35) or TEA (Group T, n = 35) within a multimodal regimen. Co-primary outcomes were intraoperative hypotension and vasopressor requirement, and Numeric Rating Scale (NRS) pain scores over 48 h. Secondary outcomes included 24-h opioid consumption, adverse events, time to ambulation and length of stay. Results: Resting pain scores were comparable; TEA produced lower dynamic scores (significant at 4 h), lower 24-h opioid consumption (16.2 vs 19.6 mg, p = 0.039) and longer time to first rescue. Intraoperative hypotension (17.1% vs 42.9%, p = 0.019), vasopressor use (14.3% vs 40.0%, p = 0.017) and urinary retention (2.9% vs 22.9%, p = 0.027) were lower with ESPB, which also enabled earlier ambulation (18.2 vs 24.6 h, p < 0.001). Conclusion: ESPB provides analgesia approaching that of TEA after major abdominal surgery with greater haemodynamic stability and fewer side effects, and is an effective alternative within enhanced-recovery pathways.